2002
DOI: 10.1152/ajpendo.00044.2002
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-induced islet blood flow increase in rats: interaction between nervous and metabolic mediators

Abstract: This study investigated the mechanisms for glucose-induced islet blood flow increase in rats. The effects of adenosine, adenosine receptor antagonists, and vagotomy on islet blood flow were evaluated with a microsphere technique. Vagotomy prevented the islet blood flow increase expected 3, 10, and 20 min after injection of glucose, whereas theophylline (a nonspecific adenosine receptor antagonist) prevented the islet blood flow increase from occurring 10 and 20 min after glucose administration. Administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 49 publications
7
62
1
Order By: Relevance
“…The assessment was done by an injection of marked microspheres with rapid (10 s) killing of the animals following injection [13]. Thus the results described in those studies may not represent dynamic change in flow as assessed in the current study.…”
Section: Discussionmentioning
confidence: 88%
“…The assessment was done by an injection of marked microspheres with rapid (10 s) killing of the animals following injection [13]. Thus the results described in those studies may not represent dynamic change in flow as assessed in the current study.…”
Section: Discussionmentioning
confidence: 88%
“…The physiological and/or metabolic events underlying the increase in islet blood flow under these circumstances are unknown. However, we believe that it could reflect an increased metabolism of the islets, since we have recently shown that this can lead to a pronounced increase in islet blood flow in other models, in which the major mediator of the response seems to be adenosine (Carlsson et al 2002). It can also be speculated that growth factors involved in the regeneration of islets (see Nielsen et al 1999) can influence islet blood flow, but this notion remains hypothetical.…”
Section: Discussionmentioning
confidence: 91%
“…Islet blood perfusion is normally tightly regulated at the arteriolar level by nervous, endocrine and metabolic mechanisms [12,13]. A dose-and time-dependent preferential increase in blood flow is induced by glucose [13,14].…”
Section: Introductionmentioning
confidence: 99%